Biological Activity and Applications of Natural Compounds - Seca, Ana M. L; Moujir, Laila Moujir; Sharopov, Farukh (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Nature represents an amazing source of inspiration, since it produces a great diversity of natural compounds selected by evolution, which exhibit multiple biological activities and applications. A large and very active research field is dedicated to identifying biosynthesized compounds, to improve/develop new methodologies, to produce/reuse natural compounds, and to assess their potential for pharmaceutical, cosmetic and food industries, among others, and additionally, to understand their mechanism of action. This book is dedicated to presenting the most recent results on the development of natural compounds' applications. Ten original research works, organized by applications, and two reviews are included. Each of them contributes to the knowledge advance, insofar as they present new applications for known products, new methodologies to obtain new products, or the evaluation of a given application, with the applications related to health promotion being the most frequently considered. These works are significant contributions and reinforce the dynamic field of natural products' applications.